GUILT IN JEFF ZENTNER’S NOVEL GOODBYE DAYS - Caniago, Desriani; Suhadi, Muhammad Fatih (Universitas Islam Sumatera Utara, 2025)
This study presents a psychological analysis of guilt and the journey toward self-redemption as depicted in Jeff Zentner's novel, Goodbye Days. Employing a qualitative descriptive method, the research meticulously examines the psychological turmoil of the protagonist, Carver Briggs, who is consumed by guilt after a tragic accident claims the lives of his three best friends—an accident he believes he caused by sending a text message. The analysis is framed within Bruce Narramore's theoretical framework on guilt, exploring its objective and subjective categories, including fear of punishment, loss of self-esteem, and feelings of isolation. The findings reveal the profound manifestations of Carver's guilt, which materialize through somatic complaints such as panic attacks, a depressed mood, self-condemnation, and acts of self-punishment. The study concludes that Zentner’s narrative portrays guilt not merely as a destructive force but as a complex and transformative psychological process. Ultimately, the novel illustrates that the path to recovery and self-forgiveness is arduous, requiring the individual to confront their pain and make peace with themselves before achieving redemption.